Exploring features and opportunities of rapid-growth wine firms in Chile - Cancino, Christian A.; Román, Jorge J.; Gallizo, José L. (Universidad Icesi, 2017)
While much has been studied regarding the wine industry in Spain and France, little has been studied in developing countries. The aim of this work is to study the characteristics of dynamic wine firms in Chile. This paper presents qualitative research and reports six cases of wine companies, where several variables are analyzed according to Barringer, Jones and Neubaum framework. These variables include prior experience, founders’ knowledge regarding large company management, the use of strategic-planning systems and the use of new technology in the majority of its production. The results of this research could prove insightful for wine entrepreneurs looking to enhance their growth, based on greater differentiation and innovation, and not only on being competitive in pricing
Exploración de las características y oportunidades de empresas vitivinícolas de rápido crecimiento en Chile
Mientrasmucho seha estudiado sobre la industria vitivinícola enEspana˜ y enFrancia,poco seha estudiado en países en desarrollo. El objetivo de este trabajo es estudiar las características de emprendimientos vitivinícolas dinámicos en Chile. El trabajo presenta un estudio cualitativo y reporta seis casos de estudio, donde una serie de variables son analizadas según el modelo de Barringer, Jones y Neubaum. Entre estas variables destacan: experiencia previa, conocimiento de fundadores en gestión de grandes negocios, uso de sistemas de planificación estratégica y uso de nuevas tecnologías en la mayor parte de su producción. Los resultados de este trabajo podrían ser interesantes para emprendedores vitivinícolas que buscan potenciar su crecimiento con diferenciación e innovación, y no solo compitiendo en costo.
Keywords: Chile; Industria; Emprendimientos; Innovación industrial